The Impact of the Mother Tongue on English Language Acquisition Among ESL Learners in the Sri Lankan Context - Mohamed Ismail Reesma Sheroon; MJF Sujani; MB Nowzath; MR. Rishad Muhammed (COMPETITIVE: Journal of Education, 2025)
The research aims to explore the challenges Grade 8 students at KM/KM/Shams Central College face in learning English due to the influence of their mother tongue, Tamil. It seeks to identify how Tamil language structures, such as sentence order and phonetic features, interfere with English learning, and to examine sociocultural factors like attitudes, language anxiety, and exposure that affect motivation and success. The study also evaluates the impact of linguistic interference on grammar, pronunciation, sentence structure, and vocabulary. Finally, it aims to propose effective teaching strategies to minimize Tamil's influence and enhance English proficiency, with a particular focus on rural educational contexts. A mixed-methods approach was employed, combining quantitative pretest and posttest assessments with qualitative data from structured questionnaires and semi-structured interviews with both students and teachers. The findings indicate that Tamil interference significantly contributes to challenges in English grammar and pronunciation, particularly in the misuse of articles, prepositions, and word order, as well as pronunciation errors involving sounds not found in Tamil. While the interventions implemented, such as task-based learning and pronunciation exercises, showed measurable improvements, sociocultural factors like anxiety and limited exposure to English outside the classroom remained barriers. The study concludes that effective English language acquisition requires addressing both linguistic interference and sociocultural challenges. Recommendations include incorporating communicative language teaching, increasing exposure to English in daily life, and providing professional development for teachers. Future research should explore the long-term impact of these strategies and the potential of technology in overcoming these challenges.